Involuntary Admissions, and Treatments (TSO) for Individuals Suffering from Schizophrenia: A Reflection on Patient Safety, and Quality of Care - Calzolari, Fabio (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 4 (2019): October-December 2019DO - 10.14456/nujst.2019.38, 2019)
Introduction : Since the Italian Mental Health Act of 1978, public attention on the outcomes of Involuntary Hospital Treatment (TSO) for people struggling with Schizophrenia (SCZ) has increased. The practice is controversial because it goes against the Human Rights standards. Against this background, the author investigates factors linked to coercive measures, and personal experiences of acute care. He hypothesizes that limitation of freedom negatively affects the quality of the therapeutic relationship (TR). Materials, and Methods : Semi structured qualitative interviews (QIs) of individuals (n = 20) who were eligible for inclusion if the following criteria applied: [1] DSM-V diagnosis of Schizophrenia; [2] Having received at least one TSO; [3] Being outpatients; and [4] having emotional, and cognitional stability. The interview text was transcribed verbatim and analyzed by means of a phenomenological method. Results. The cohort described TSO as an unwelcome, and intrusive practice. Even if clinicians often justified the admissions, only a few patients gave an account of being told why their agency was eroded. Moreover, TSO damages Self-confidence, and trust in public services. Inasmuch, to prevent distress and avoid an outflow of so-called psychiatric refugees, the Italian government needs to improve joint crisis plans between patients, families, and medical equips. Discussion. The Republic of Italy does not have asylums but community-centers, and psychiatric wards within general hospitals. The Law No. 833 of 23 December 1978 established the possibility of a TSO for a period of 1-7 days in the simultaneous presence of [1] Psychiatric conditions that require urgent therapy; [2] Patient’s refusal of assistance; and [3] Circumstances that do not consent other less-invasive strategies. To author’s knowledge, this is one of the few qualitative reflections done on the pros and cons of adult Psychiatry, in Italy.  The survey adds valuable information regarding degree, and predictors of loss of autonomy, dignity, and the possibility of interpersonal contact. Keywords : Schizophrenia, TSO, Human Rights, Therapeutic Relationship, Law No. 833.